INCORPORATING LESSON PLAN IN DEVELOPING AN ITINERARY FOR A TOUR PACKAGE TO PROMOTE LOCAL CULTURE: A CASE STUDY IN KAMPOENG WISATA CINANGNENG, BOGOR REGENCY - Sari Rejeki; Imani Satriani; Qoute Nuraini Cahyaningrum (Universitas Wiralodra, 2024)
Studies on tourism in Bogor have focussed on community-based tourism, natural and outdoor tourism, the preservation of natural environment and culture of its people. This research in particular focuses on specifically combining local culture and language learning.The aim of this study is to shed light on how lesson plans can be incorporated in developing existing tour packages of a tourist attraction that promotes local culture. It proposes lesson plan by Brown and the notion of Engage-Study-Activate by Harmer. Using qualitative approach, Kampoeng Wisata Cinangneng located in Bogor Regency is chosen as case study. As the tour packages in Kampung Wisata Cinangneng are popular amongst elementary school students to teenagers, the lesson plans are limited to these age groups. Data collection techniques applied in this study were literature studies, observations, interview and documentation. The findings also support the use of six stages for analysis to design and develop an itinerary as part of a tour package. The stages involve determining a tourist attraction that promote local culture, studying its tour packages or programs to seek the target market and what it advertises, identifying unique local culture advocated from the tourist destination, determining local culture which can be incorporated with language learning, researching further the local culture selected. The last stage entails, applying Browns’ lesson plan and Harmers’ Engage-Study-Activate in the procedure. The stages of analysis proposed is seen crucial to make tour packages not only entertaining but also have educational value. In this case, preserving and promoting local culture. Drawing on the results, this study gives an advantage in the applicability of writing a lesson plan that focuses on local culture and language learning for an itinerary.